Virtual Social Movements and Gen-Z Activism: A Study of the #TolakOmnibusLaw Movement in the Digital Space - Ginna Novarianti Dwi Putri Pramesti (Return : Study of Management, Economic and Bussines, 2025)
The rise of digital platforms has reshaped political participation, particularly among Generation Z (Gen-Z). In Indonesia, the #TolakOmnibusLaw movement represents a significant shift in youth activism, leveraging digital spaces to challenge the government's controversial policy. This research aims to analyze the role of Gen-Z in shaping digital activism through the #TolakOmnibusLaw protest, using digital ethnography and social network analysis (SNA) to explore how social media facilitated online political mobilization. The study employs digital ethnography to examine the cultural practices of Gen-Z activists, focusing on their use of memes, TikTok videos, and online discourse. Social network analysis is utilized to trace the spread of the protest across digital platforms, identifying key nodes and influential actors. Findings suggest that digital platforms, particularly Twitter and TikTok, were essential in amplifying the protest, with fandom groups and influencers playing a central role in spreading the message. Despite challenges related to the effectiveness of digital activism, the research indicates that Gen-Z’s participation in the #TolakOmnibusLaw protest led to significant political discourse and youth engagement in Indonesia’s democracy. The study recommends further exploration of hybrid activism, combining digital engagement with offline participation, as a crucial avenue for enhancing youth political involvement in the future.